Evidence for the Requirement of ITAM Domains but Not SLP-76/Gads Interaction for Integrin Signaling in Hematopoietic Cells - Abtahian, Farhad (American Society for Microbiology, 2006)
Syk tyrosine kinase and Src homology 2 (SH2) domain-containing leukocyte-specific phosphoprotein of 76 kDa (SLP-76) are signaling mediators activated downstream of immunoreceptor tyrosine-based activation motif (ITAM)-containing immunoreceptors and integrins. While the signaling cascades descending from integrins are similar to immunoreceptors, the mechanism of Syk activation and SLP-76 recruitment remains unclear. We used an in vivo structure-function approach to study the requirements for the domains of Syk and SLP-76 in immunoreceptor and integrin signaling. We found that both SH2 domains and the kinase domain of Syk are required for immunoreceptor-dependent signaling and cellular response via integrins. While the Gads-binding domain of SLP-76 is needed for immunoreceptor signaling, it appears dispensable for integrin signaling. Syk and SLP-76 also are required for initiating and/or maintaining separation between the blood and lymphatic vasculature. Therefore, we correlated the signaling requirement of the various domains of Syk and SLP-76 to their requirement in regulating vascular separation. Our data suggest ITAMs are required in Syk-dependent integrin signaling, demonstrate the separation of the structural features of SLP-76 to selectively support immunoreceptor versus integrin signaling, and provide evidence that the essential domains of SLP-76 for ITAM signals are those which most efficiently support separation between lymphatic and blood vessels.